CONTRIBUTIONS OF MONITORING IN THE MONITOR’S ACADEMIC TRAINING: EXPERIENCE REPORT - Kercia Trajano Feitosa, Ana; Xavier Silva Barbosa, Milena; Augusto Arnes dos Santos, Ihernes (Revista Gênero e Interdisciplinaridade, 2023)
The monitoring program is a modality of extracurricular activity, focused on expanding teaching to undergraduate courses, this constitutes an integrated form in the construction of more in-depth knowledge of a given discipline. The main objective of the project was to present, in the form of an experience report, the contributions of the monitoring program in the academic training of the monitor. To carry out this work, we opted for a descriptive study, of the experience report type, carried out from the experience in voluntary monitoring. During the period in which the monitoring took place, important aspects were noted about the social relationships that are established during that time, relationships that encourage a better personal development of the monitor, a fact that was also observed by TAVARES et al. (2017) in their experience report with the monitoring program. It is emphasized that monitoring is of paramount importance as a support to students for a better quality of teaching, and encompasses disciplines and potential areas, constituting a full activity that helps in the pedagogical knowledge produced during the graduation period.